Comparison of the Arylamine N-acetyltransferase from Mycobacterium marinum and Mycobacterium tuberculosis. - Fullam, E; Kawamura, A; Wilkinson, H; Abuhammad, A; Westwood, I; Sim, E (2009)
Arylamine N-acetyltansferase (NAT) from Mycobacterium tuberculosis (TBNAT) is a potential drug target for anti-tubercular therapy. Recombinant TBNAT is much less soluble and is produced in lower yields than the closely related NAT from Mycobacterium marinum (MMNAT). In order to explore MMNAT as a model for TBNAT in drug discovery, we compare the two mycobacterial NAT enzymes. Two site-directed mutants of MMNAT have been prepared and characterised: MMNAT71, Tyr --> Phe and MMNAT209, Met --> Thr, in which residues within 6 A of the active-site cysteine have been replaced with the corresponding residue from TBNAT. Two chimeric proteins have also been produced in which the third domain of MMNAT has been replaced by the third domain of TBNAT and vice versa. The activity profile of the chimeric proteins suggests a role for the third domain in the evolutionary divergence of NAT between these closely related mycobacterial species.